2018
DOI: 10.3390/jfmk3030040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Attentional Focus Instructions on Motor Learning and Performance of Patients with Central Nervous System and Musculoskeletal Disorders: a Systematic Review

Abstract: Exercise is one of the main rehabilitative interventions, commonly used to improve performance and motor learning. During the application of attentional focus strategies, External Focus of Attention (EFA) aiming at the movement effect has been reported to have more efficacy than Internal Focus of Attention (IFA) aiming at movement characteristics in healthy subjects. There are not many studies that compare the EFA and IFA instructions in people with Musculoskeletal (MSK) and Central Nervous System disorders (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 72 publications
(242 reference statements)
0
35
0
7
Order By: Relevance
“…Potentially, the most worrying long-term outcome of CAI is the development of post-traumatic osteoarthritis 2 . Therefore, preventive initiatives are necessary to reduce the long-term consequences of these injuries 51 , and the first step towards progress in this area is to examine the walking features of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, the most worrying long-term outcome of CAI is the development of post-traumatic osteoarthritis 2 . Therefore, preventive initiatives are necessary to reduce the long-term consequences of these injuries 51 , and the first step towards progress in this area is to examine the walking features of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, the cognitive task provides an external focus which diverts attention from body sways and reduces conscious control [ 39 ]. Some studies have shown the potential of external focus to reduce postural instability during quiet standing compared to an internal focus in pwPD [ 40 ] and to improve postural instability when pwPD took dopamine medication [ 41 ]. However, if we did not find significant difference due to the dual-task, confidence interval higher limit was higher for COP pathway and ellipse area under dual-task.…”
Section: Discussionmentioning
confidence: 99%
“…Trackers could be considered as real external focus of attention (EFA). Research reported that EFAs are more effective than internal focus of attention (IFA) in terms of motor performance and learning improvements (Rossettini et al 2017) (Piccoli et al 2018). Indeed, EFAs provide a higher level of movement efficacy and kinematics across different types of tasks, skill levels and age groups (Wulf 2013).…”
Section: Discussionmentioning
confidence: 99%